Study on influence mechanism of biochar on soil nitrogen conversion. Issue 1 (31st December 2022) - Zhao, Pingnan; Wang, Shen; Liu, Dong; Li, Hongxu; Han, Song; Li, Ming
ABSTRACT: Straw had huge annual production, burning it in the air will cause serious air pollution. Burning straw into biochar and returning biochar to the field will not only make effective use of straw resources, but also improve soil quality. Different preparation conditions and addition levels of biochar were used to investigate the ammonia nitrogen, nitrate nitrogen, and total nitrogen contents in the soil leaching solution. The results showed that biochar had a favorable adsorption effect on ammonia nitrogen, the cumulative leaching of ammonia nitrogen reduced by 80.16% in the 2% and 400°C biochar addition treatment compared to that without adding biochar. The final leaching solution electrical conductivity value of the experimental group of biochar prepared at 500°C with 1% addition was the highest at 445 μS/cm. Sequencing of microorganisms revealed that biochar altered the structure and abundance of the soil microbial community, particularly increased the relative abundance of nitrifying bacteria.